The Contribution of Political Education to the Level of Party-ID among Adolescents - Kamila, Aghna Afifah Dwi Cahya; Gistian, Disalsa Awalia; Munawar, Rizky (Candidate: Jurnal Sains Politik, 2025)
Indonesia is a country that implements a general election system to elect its president. However, this contrasts with the low level of party identification (party-id) and the absence of political education to address this issue. The purpose of this research is to determine the extent of the impact of political education on the level of party-id. The research method uses a qualitative approach by collecting secondary data from previous studies, interviews, document studies, observations, and more. This research focuses on conducting structured interviews with informants by posing several questions and performing observational studies on several journals. The scope of this study is limited to adolescents in the city of Bandung, aged between 17 and 21 years. This paper states that political education has a significant influence on the increase in party-id levels. This research will contribute to understanding the importance of political education for adolescents, thus helping to address the issue of low party-id levels and is expected to increase party-id levels in Indonesia.